Between self-determination and dependency : Jamaica's foreign relations 1972-1989 (UWI Press KingstonJM, 2000)
Analyzes the nature and progress of Jamaica's foreign relations during the period 1972-1989. Argues that the relative autonomy of the Jamaican state with regard to the conduct of foreign relations was reduced because of the evolution of a new international regime.
Keywords: SELF DETERMINATION